Sustainable urban transportation planning: Integrating an electrified metro system into Kampala metropolis - Kimuli, Ismail; Kirabira, John Baptist; Nkambwe, Ismael; Nakyejwe, Saadat L.K.; Lubwama, Michael; Sendawula, Kasimu; Nabaggala, Nashua K (Elsevier Ltd, 2024)
Electrified metro critical.•Policy shifts vital.•Multi-modal integration.•Renewable energy focus.•Kampala-specific solutions. With the United Nations (UN) predicting that 60% of the global population will reside in cities by 2050, sustainable transportation planning is a prominent global trend. This study examines Kampala's transportation sustainability and addresses existing knowledge gaps. It leverages the TIMES-VEDA model, an acronym for “The Integrated MARKAL-EFOM System - Versatile Data Analyst.” TIMES-VEDA is an engineering optimizer used to explore four scenarios: Business-as-Usual (BAU), Reduction in Electricity Consumption (REC), Renewable Electricity Portfolio (REP), and Carbon Reduction Target (CRT). These scenarios analyze the inherent aspects of the Kampala metropolis energy system, providing a foundation for evidence-based decision-making. The approach aligns with the United Nations’ Sustainable Development Goals (UN's SDGs 7, 11, & 13), Uganda's Vision 2040, and the third National Development Plan (NDPIII). The analysis demonstrates that sustainability is within range and highlights the imperative of a holistic approach, the potential of mass rapid transit, anchored by an electrified metro system, to advance green mobility. It sheds light on sustainable practices and trade-offs among distinctive pathways, suggesting a mix of policy measures to combat climate change. The KAMPALA-TIMES model, a bottom-up framework, reveals that a region-specific policy package, particularly the CRT scenario, achieves significant decarbonization, promoting eco-friendly multimodal transportation and paving the way for a more sustainable future for Kampala until 2060. The findings inform policy on urban planning and sustainable transportation that is adaptable elsewhere, ensuring long-term environmental and economic resilience.